2017
DOI: 10.1189/jlb.4ru0317-111r
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype and function of preterm infant monocytes: implications for susceptibility to infection

Abstract: The extreme vulnerability of preterm infants to invasive microbial infections has been attributed to "immature" innate immune defenses. Monocytes are important innate immune sentinel cells critical in the defense against infection in blood. They achieve this via diverse mechanisms that include pathogen recognition receptor- and inflammasome-mediated detection of microbes, migration into infected tissues, and differentiation into Mϕs and dendritic cells, initiation of the inflammatory cascade by free radicals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 104 publications
4
46
0
Order By: Relevance
“…The lack of deficiencies in overall gene expression or cytokine production in monocytes from preterm chorioamnionitis‐unexposed infants compared to term infants was unexpected, as deficient monocyte responses to PRR‐stimulation in preterm infants are widely described . However, Lissner et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of deficiencies in overall gene expression or cytokine production in monocytes from preterm chorioamnionitis‐unexposed infants compared to term infants was unexpected, as deficient monocyte responses to PRR‐stimulation in preterm infants are widely described . However, Lissner et al .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of deficiencies in overall gene expression or cytokine production in monocytes from preterm chorioamnionitis-unexposed infants compared to term infants was unexpected, as deficient monocyte responses to PRR-stimulation in preterm infants are widely described. 6 However, Lissner et al also observed minimal transcriptional differences between purified monocytes from term infants and adults (following LPS or Listeria monocytogenes-stimulation), 16 despite reports of impaired monocyte-dependent cytokine responses to LPS in neonates compared to adults. 17,18 One possible mechanism is regulation of monocyte function through extrinsic factors either in cord plasma or from other mononuclear populations, which were removed in our experiments and those of Lissner et al A variety of soluble mediators capable of modulating monocyte responses are present in plasma, including adenosine, 19 the antimicrobial peptide LL-37 20,21 and the alarmins S100A8/A9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The critical nature of this period is exacerbated by Th 2 -skewed adaptive immunity [3, 4] and a reliance on transferred maternal antibodies [5], resulting in a dependence on innate immune mechanisms for protection [6, 7]. However, neonatal innate immune cells such as neutrophils [8–11], monocytes [12, 13], and dendritic cells [14] are also limited in their responses compared to adult cells. This immunosuppressed state has disadvantages such as predisposing newborns to severe infection and weakening their response to vaccination [2, 15].…”
Section: Introductionmentioning
confidence: 99%